First report of natural infection of Vigna mungo var. silvestris L. by Groundnut bud necrosis virus, a tospovirus - AKRAM, Mohammad; NAIMUDDIN, Kamal (Phytopathologia Mediterranea, 2010)
In the autumn of 2008, Vigna mungo var. silvestris growing in the experimental field of the Indian Institute of Pulses Research, Kanpur, India, showed chlorosis around some lateral veins and vein branches (mainly near the leaflet margin), downward curling of the leaf margins, necrosis of the stems and petioles, and twisting of the leaflets. Disease incidence was 20%. Symptoms indicated that the cause was Groundnut bud necrosis virus. The virus was identified on the basis of the symptoms on the diagnostic host, and the reverse transcription polymerase chain reaction (RT-PCR) using specific primers of the NSm and NP genes. To our knowledge this is the first report of Groundnut bud necrosis virus on V. mungo var. silvestris.